2013
DOI: 10.1111/corg.12013
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Board Interlocks on Auditor Choice and Audit Fees

Abstract: Manuscript Type Empirical Research Question/Issue This paper uses unique Danish data to examine whether non‐executive directors draw on both direct and indirect ties in the network of interlocking directorates to impact auditor choice, and whether this impact has consequences for audit fees. Research Findings/Insight The paper finds clear evidence that non‐executive directors draw on their networks to impact auditor choice, and evidence that clients pay an audit fee premium when non‐executive directors are con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 108 publications
(204 reference statements)
4
74
1
Order By: Relevance
“…Initially, this study confirmed that interlocks impact auditor selection (Davison et al, 1984;Johansen & Pettersson, 2013), but also that Danish interlocks have a strong tendency to form complex, closure-like network configurations, which might enable information flow and managing decisions across the alliances. In respect to other studies on strategies for establishing interlocking directorships (Mizruchi & Stearns, 1988;Stokman et al, 1985;Pfeffer & Salanc, 1978;Useem, 1982) and reasons for auditor selection and change (Beattie & Fearnley, 1995;Magri & Baldacchino, 2004;Woo & Koh, 2001), the findings showed that, in both contexts, relationships tend to either exist between those that are reputable, or to emerge towards those that are reputable.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Initially, this study confirmed that interlocks impact auditor selection (Davison et al, 1984;Johansen & Pettersson, 2013), but also that Danish interlocks have a strong tendency to form complex, closure-like network configurations, which might enable information flow and managing decisions across the alliances. In respect to other studies on strategies for establishing interlocking directorships (Mizruchi & Stearns, 1988;Stokman et al, 1985;Pfeffer & Salanc, 1978;Useem, 1982) and reasons for auditor selection and change (Beattie & Fearnley, 1995;Magri & Baldacchino, 2004;Woo & Koh, 2001), the findings showed that, in both contexts, relationships tend to either exist between those that are reputable, or to emerge towards those that are reputable.…”
Section: Discussionsupporting
confidence: 71%
“…In an Australian context, Davison et al (1984) found that links between companies audited by the same audit firm can, to a considerable extent, be explained by links between those same companies when they have a director in common. On the other hand, by focusing on an experience-based demand mechanism, Johansen and Pettersson (2013) found that interlocks in Denmark have a strong impact on the selection of auditors and audit fees. The gap found in previously proposed framework urges bridging the seemingly disparate bodies of theory by discussing the question of how two reputation-driven demands are mutually negotiated through mechanisms of interlocking directorships and auditor selection.…”
Section: Reputation In the Contexts Of Auditing And Interlocking Dirementioning
confidence: 99%
“…This is because there is a whole range of studies that deal with the board and director interlock [15,[22][23][24][25][26] and ownership interlock [27][28][29], but there are few studies that consider these two types of relationship jointly [30], especially in emerging markets like Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…In this arrangement of extended interlocking, the promoters, who have substantial control over firm executives, may appoint their favorite audit committee members on the multiple firms in the business group, and their social ties gets further fillip with the inclusion of auditors of their choice. Johansen and Pettersson (2013) find that in the interlocked relationship audit committee members and promotors generally employ the same audit firm in the business group firms. The increasing familiarity between the participants of the extended interlocking can result in lesser monitoring of managerial actions and diminishing credibility of audit quality, which can result in lower financial reporting quality.…”
Section: Prior Literature and Hypotheses Developmentmentioning
confidence: 85%
“…However, there are several other types of services that audit firms can still do for their client firms. In the extended interlocking relationship, the audit committee members, and promotors often employ the same auditor in various firms in the business group (Johansen and Pettersson, 2013). The audit committees, executive directors and promoters of the client firms may prefer their audit firms to do the NAS too.…”
Section: Corporate Governance Variablesmentioning
confidence: 99%